Dementia and Elderly. An Analysis of Judicial Protection Measures: Disability and Involuntary Commitment (Revista Iberoamericana de Bioética, 2020)
Progressive population aging leads to an increase in dementia cases. The law provide some personal protection tools, mainly in the form of judicial decisions on incapacitation and involuntary confinement. The analysis of the juridical framework of such institutions and their possible practices reveals the need for more flexible and adaptable resources. Neuroscience can improve evidence in order to check the degree of personal competence. International Principles on Dementia are based on the fundamentals of bioethics.
Keywords: dementia; elderly; protection measures; neuroscience; bioethics